Court/Judicial records as a historical source to analyse labor relations - Lemiez, Griselda (Revista General de Información y Documentación, 2019)
In the following article, the data on labor conflicts in court records that occurred in the cement companies of Olavarría (Buenos Aires, Argentina) will be analyzed. A selection of records was made that find a direct relationship with the reconstruction of conflicts, as part of labor relations in the cement industry, during the period 1940-1970. We believe that the application of these unique sources to various studies will allow us to assess the importance of their use and enrich historical research.